(untitled) (Jurnal Simki Economic, 2022)
This study aims to determine the effect of Interest Coverage Ratio, Basic Earning Power and Earning Per Share partially and simultaneously on the stock price of PT Indofood Sukses Makmur Tbk. Investors must be careful in making investment decisions because many factors affect stock price including Interest Coverage Ratio, Basic Earning Power and Earning Per Share. This is reinforced by looking at the financial statements and experiencing fluctuations every period. Referring to several opinions of financial experts and the results of previous studies which state that the higher the Interest Coverage Ratio, Basic Earning Power and Earning Per Share, the higher the influence on stock price. The research method used is a quantitative method. The type of data used is secondary data from the 2011-2020 annual report published by the company on the official website. The results of this study show that partially Interest Coverage Ratio has a very weak relationship, Basic Earning Power has a weak relationship, Earning Per Share has a moderate relationship and partially has no significant effect on stock price, then simultaneously Interest Coverage Ratio, Basic Earning Power and Earning Per Share has a strong relationship and there is no significant effect on stock price.